Attorney general: role and powers - Ali Mohamed, Ashgar Ali; Mallow, Muzaffar Syah (The Malaysian Current Law Journal Sdn Bhd, 2014)
The Attorney General of Malaysia (AG) is the principal legal adviser to the Government of Malaysia. Section 376(1) of the Criminal Procedure Code provides that the Attorney General shall be the Public Prosecutor and shall have the control and direction of all criminal prosecution and proceeding under the code. The powers with regards to prosecution are contained in art. 145(3) of the Federal Constitution. The Attorney General can be regarded as the chief law officer of the Executive Council. The responsibilities stemming from this role are unlike those of any other Cabinet member. The role has been referred to as ‘judicial-like’ and as the ‘guardian of the public interest’. There are various components of the Attorney General’s role. The Attorney General has unique responsibilities to the State, the courts, the legislature as well as towards the executive branch of government. While there are different emphases and nuances attached to these there is a general theme throughout all the various aspects of the Attorney General’s responsibilities that the office has a constitutional and traditional responsibility beyond that of a political minister. The role and functions of the AG including the various divisions or departments under the AG’s chambers are discussed in this chapter.